PARACETAMOL POISONING IN A CAT AND ITS TREATMENT - P. Pothiappan; T. Muthuramalingam; R. Sureshkumar; G. Selvakumar; M. Thangapandiyan; G. D. Rao (Indian Journal of Veterinary and Animal Sciences Research, 2024)
A two year old male cat was presented to the Emergency and Critical Care Unit with a history of inappetence after paracetamol 300 mg (Half tablet of 600 mg) administration overnight. On clinical examination the cat had a mild elevation of vital signs. Based on history and clinical signs the case was diagnosed as paracetamol poisoning and treated with activated charcoal a total dose of 3 g)orally and N-acetyl cysteine intravenously at 140 mg/kg along with Ringer’s lactate, 10 ml/kg b.wt. The owner was advised to administer Nacetyl cysteine at 70 mg/kg orally for every 6 hours for five times. After treatment the cat was recovered successfully.